SUPPLY CHAIN AGILITY IN HUMANITARIAN LOGISTICS - Bányai, Tamás (Advanced Logistic Systems - Theory and Practice, 2016)
The supply chain agility plays a crucial role in logistics processes. The agility is of particular importance in humanitarian logistics, where the main aim is to save life and reduce suffers; food, pharmacy and accommodation must be transported to the location of natural or man-made disasters. The supply chain agility is influenced by different factors of logistics processes: alertness, accessibility, decisiveness, swiftness and flexibility. There are in the literature different approaches describing supply chain of humanitarian logistics processes. Within the frame of this paper, the author describes a new model of the supply chain of humanitarian logistics. After a careful literature review, this paper introduces an approach, which integrates not only the technical and technological aspects of the operation but also the design and optimisation of processes. This work considers the unique requirements of disasters and focuses on the agility of supply chain process. The present paper contributes to the system theory of humanitarian logistics and offers new insights in methodological theory, paving the way for further research works on this topic.